Engineering mesophilic GH11 xylanase from Cellulomonas flavigena by rational design of N-terminus substitution - Tian, Wenzhuo; Zhang, Ziyang; Yang, Cuiping; Li, Piwu; Xiao, Jing; Wang, Ruiming; Du, Peng; Li, Nan; Wang, Junqing (Frontiers in Bioengineering and Biotechnology, 2022)
Xylanase, a glycoside hydrolase, is widely used in the food, papermaking, and textile industries; however, most xylanases are inactive at high temperatures. In this study, a xylanase gene, CFXyl3, was cloned from Cellulomonas flavigena and expressed in Escherichia coli BL21(DE3). To improve the thermostability of xylanase, four hybrid xylanases with enhanced thermostability (designated EcsXyl1–4) were engineered from CFXyl3, guided by primary and 3D structure analyses. The optimal temperature of CFXyl3 was improved by replacing its N-terminus with the corresponding area of SyXyn11P, a xylanase that belongs to the hyperthermostable GH11 family. The optimal temperatures of the hybrid xylanases EcsXyl1–4 were 60, 60, 65, and 85 ℃, respectively. The optimal temperature of EcsXyl4 was 30 ℃ higher than that of CFXyl3 (55 ℃) and its melting temperature was 34.5 °C higher than that of CFXyl3. After the hydrolysis of beechwood xylan, the main hydrolysates were xylotetraose, xylotriose, and xylobiose; thus, these hybrid xylanases could be applied to prebiotic xylooligosaccharide manufacturing.